2016
DOI: 10.1080/21580103.2015.1135827
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organic manure and chemical fertilizer on the growth and nutrient concentrations of yellow poplar (Liriodendron tulipiferaLin.) in a nursery system

Abstract: View related articlesView Crossmark data Citing articles: 30 View citing articlesThe effects of organic manure and chemical fertilizer on the growth and nutrient concentrations of yellow poplar (Liriodendron tulipifera Lin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(107 citation statements)
references
References 18 publications
10
91
0
6
Order By: Relevance
“…Organic fertilizer application in soil increases or stabilizes the soil pH [4,33,34]. However, the findings of this study indicated that M1, MS1, M2, and MS2 amendments were more effective in increasing the soil pH, which is consistent with the previous results of Han et al [35] and Das et al [9]. Adding various organic supplements to the soil enhances the accumulation of basic macronutrients, especially N, K, and P, as well as soil organic matter [16].…”
Section: Discussionsupporting
confidence: 89%
“…Organic fertilizer application in soil increases or stabilizes the soil pH [4,33,34]. However, the findings of this study indicated that M1, MS1, M2, and MS2 amendments were more effective in increasing the soil pH, which is consistent with the previous results of Han et al [35] and Das et al [9]. Adding various organic supplements to the soil enhances the accumulation of basic macronutrients, especially N, K, and P, as well as soil organic matter [16].…”
Section: Discussionsupporting
confidence: 89%
“…Photosynthesis activity increases in the case of sufficient K (Hu et al, 2015). Manure compost is a robust source of plant nutrients (Han, An, Hwang, Kim, & Park, 2016). The addition of organic materials improves the plant rhizosphere, making the soil structure crumble and soil aeration better, so that root plants more easily absorb K nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…Applications of chemical fertilizers and organic compost have both good and adverse effects on plant growth and the soil [1]. Chemical fertilizers are inexpensive, contain high nutrients, and are readily available to be taken up by plants.…”
Section: Introductionmentioning
confidence: 99%